GIS Method in Tourism (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
GIS (geograhic information system) is currently becoming popular among the nations when it comes to tourism GIS shows huge effect such as giving exact information base to visitors who should be sure in where they are safe and there are enough things which are deserve to make effort to see. As well as GIS is connected with portals and new digital media.